To estimate the power spectral density of the moment on the milling drum of the road mill at the design stage - Fomin K.V. (Научно-технический вестник Брянского государственного университета)
Milling is the main workflow for trailer and self-propelled road mills, recyclers and process complexes for road construction and repair. Their application allows achieving high quality of works, to provide complex mechanization and to provide high productivity. In process of technological operation, sharply variable random loads occur on working element. The paper discusses the model of forming the resistance moment on the mill. The case is presented when it consists of sections, each of which has several cutting planes, with different number of knives in the plane and radius along the ends of cutting elements. The article proposes a method of calculating mutual spectral densities of resistance moments at different sections of the mill. Expressions are obtained, which make it possible at design stage to calculate spectral density of moment on working member taking into account its design, angular velocity, random variability of physical and mechanical properties of treated medium, depth of milling. Probabilistic characteristics of the mill loads serve as initial information for dynamic analysis of the drive system and unit design, its strength analysis, selection of optimal parameters and operating modes.